(untitled) (Indian Journal of Public Health Research & Development, 2020)
Fatigue can affect work productivity. Based on data obtained from Oil Company Padalarang in 2013 had 16 fuel truck accidents, work fatigue factor ranks 4th (25%). This study aims to determine the factors associated with work fatigue in fuel truck drivers Oil Company in 2015. The research design used was analytic survey study with Cross Sectional research design. With the number of cases 60 respondents, sampling techniques using Quota Sampling. Data collection using reaction timer, questionnaires and interviews. Data analysis using univariate and bivariate (Chi-Square) analysis. The results showed a description of work fatigue 61.7%, age at risk (?40 years) 65.0%, abnormal nutritional status 45.0%, work period (?5 years) 63.3% and heavy workload 38.3 %. It is known that there is a relationship between fatigue and age with P Value (0.002), work period with P Value (0.001), workload with P Value (0.018) and there is no relationship between work fatigue and nutritional status with P Value (0.936). It is recommended to provide a resting place for fuel truck drivers, making a policy to regulate the distance of fuel delivery between drivers who are old and young, do a health check before and after sending fuel and maintain a pattern of rest or sleep for fuel truck drivers.